Die boer in Suidwes-Afrika - Trümpelmann, Georg Paul Johannes; Coetzee, Colin G.(Colin Gerhardus),1918- (Stellenbosch : Stellenbosch University, 2012)
Die boer in Suidwes-Afrika' is a DPhil thesis, University of Pretoria.